2022
DOI: 10.3390/ma15062164
|View full text |Cite
|
Sign up to set email alerts
|

Progress in the Development of Graphene-Based Biomaterials for Tissue Engineering and Regeneration

Abstract: Over the last few decades, tissue engineering has become an important technology for repairing and rebuilding damaged tissues and organs. The scaffold plays an important role and has become a hot pot in the field of tissue engineering. It has sufficient mechanical and biochemical properties and simulates the structure and function of natural tissue to promote the growth of cells inward. Therefore, graphene-based nanomaterials (GBNs), such as graphene and graphene oxide (GO), have attracted wide attention in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 132 publications
(141 reference statements)
0
21
0
Order By: Relevance
“…The lyophilized coverslips were dried, and a droplet (15 µL) of material was deposited in the center. The droplets were then heated at 85 • C for 2 1 2 h, to remove any excess moisture and to make the material obtain a gel-like composition. The procedure was conducted at RT and in the absence of light.…”
Section: Photoresist Preparationmentioning
confidence: 99%
See 3 more Smart Citations
“…The lyophilized coverslips were dried, and a droplet (15 µL) of material was deposited in the center. The droplets were then heated at 85 • C for 2 1 2 h, to remove any excess moisture and to make the material obtain a gel-like composition. The procedure was conducted at RT and in the absence of light.…”
Section: Photoresist Preparationmentioning
confidence: 99%
“…More specifically, 15 µL of the material was deposited in the center of a coverslip, which was spin-coated at 4000 rpm for 40 s with an acceleration step of 500 rpm/s. The thin films were then heated for 2 1 2 hours at 85 • C to remove any excess moisture. Afterward, they were placed under a UV light overnight to polymerize the resins.…”
Section: Thin Film Preparation and Contact Angle Measurementsmentioning
confidence: 99%
See 2 more Smart Citations
“…Graphenes are used in a broad variety of applications, including quantum physics, nanoelectronics, catalysis, nanocomposites, and sensor technology [ 9 , 10 ]. It has been also reported that they exhibit strong antibacterial toxicity [ 11 , 12 ] and are very useful in several medical applications, including therapeutics, diagnostics, and regenerative medicine [ 13 , 14 ]; therefore, one main focal point of the application of graphene-based materials is in the field of nanomedicine. Many studies have attempted to exploit them for drug delivery or imaging, since they can solubilize and bind drug molecules because of their large surface area and delocalized π electrons [ 13 , 15 ].…”
Section: Introductionmentioning
confidence: 99%